A CASE OF LOBULATED CAPILLARY HEMANGIOMA OF THE NOSE WITH LINEAR AND WHORLED NEVOID HYPERMELANOSIS - T. SANTHI (International Journal of Pharma and Bio Sciences, 2015)
Nasal lobular capillary hemangioma (LCH) is a rare tumor of the nose and paranasal sinuses. The exact etiopathogenesis is still unknown. Linear and whorled nevoid hypermelanosis (LWNH) is also a rare skin condition. Both are associated with chromosomal and systemic anomalies. A case of a 24 year old female patient who presented with epistaxis and nasal obstruction is reported. She was found to have associated LWNH. The various etiological factors and management are discussed. This is a unique case and first of its kind reported in the literature.